Potret Dinasti Politik dalam Pengisian Jabatan Administratif - Darmansyah, Ramlan; Syahrani, Siti Desma; Harirah MS, Zulfa (Journal of Political Issues, 2020)
Constitutional political dynasties can be regulated in such a way, but in the context of a democratic state it is considered bad because it prevents the freedom of the people from participating in contesting political positions and bureaucratic positions within the Regional Government. The author discusses the practice of political dynasties that had been established by the elected regional heads over the power they already possessed. The issues raised in this study are (1). How is the practice of political dynasties carried out by the Regional Government in Riau Province? And what are the implications of political dynasties in Riau Province that have never been healed? Data collection in this research was carried out by studying literature by collecting related documents both journals, books and news in the mass media. The results of this study indicate that in the regional government environment in Riau Province whether the Governor, Regent and Mayor are considered to have built political dynasties by inaugurating families, namely children, wife, brothers and sisters to fill strategic positions in the Province, Regency and City. Finally, the practice of political dynasties has an adverse effect on governance because the practice of political dynasties is an early form of abuse of power. Among them is the flourishing of corrupt and collusive practices as well as blocking the freedom of people who have the competence to compete in filling strategic positions within the Regional Government.